Development of Guided Discovery Learning Voltaic Cell E-LKPD for Class XII SMA/MA Students - Servi Farda Yola; Desy Kurniawati (Universitas Riau, 2023)
This study aims to develop voltaic cell E-LKPD based on guided discovery learning. This research is research and development or Research and Development (R&D) which uses the Plomp development model. This development model consists of three stages including initial research, prototype formation, and the assessment stage. The research instrument was in the form of a questionnaire sheet. The E-LKPD was validated by 5 validators including 4 chemistry lecturers at FMIPA UNP and 1 chemistry teacher at SMA Negeri 1 Batang Anai. This data was analyzed using the Aiken'V scale to test validity, practicality test was analyzed using the percent formula, effectiveness test using the N-Gain formula. The results of the content validation test average value of 0.85 in the high category. Construct validation test results with an average value of 0.89 in the high category. Media validation test results with an average value of 0.82 in the high category. The practicality test results of students and teachers with aspects of ease of use, time efficiency, and benefits respectively with an average of 87% and 96% in the very practical category. The results of the effectiveness test were obtained with a value of 0.71 in the high category. The results of the answers to the voltaic cell E-LKPD based on guided discovery learning obtained an average of 84. Based on the results of the study it can be concluded that the developed voltaic cell E-LKPD based on guided discovery learning is valid, practical, and effective.